Strategies for Managing Information Technology Infrastructure to Improve Education Access in Remote Areas: A Comprehensive Approach to the Challenges and Solutions of Education Digitalization - Harahap, Muhammad Ade Kurnia; Mahardhani, Ardhana Januar; Murthada (PT. LITERASI SAINS NUSANTARA, 2025)
Equal access to education remains a challenge in Indonesia, especially in remote areas with limited information technology (IT) infrastructure. This study analyzes IT infrastructure management strategies to enhance education access using a literature review and qualitative methods. Data from Google Scholar and relevant websites (2018–2025) were rigorously selected, narrowing 40 articles to 18. Findings highlight key challenges: limited internet connectivity, insufficient digital devices, low digital literacy among educators, and suboptimal government policies. To address these, strategies include expanding satellite-based internet, partnering with the private sector for device provision, community-based teacher training, and empowering local communities in technology use. The government plays a crucial role in developing integrated, region-specific policies to ensure sustainable education digitalization. A comprehensive strategy is essential to reducing disparities in education access and achieving a more equitable distribution of education quality across Indonesia.